(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
This article broadly covers the issues of environmental protection, ensuring ecological sustainability and rational use of natural resources. Scientifically based ideas presented about environmental problems that arise along with human development, global warming, waste reduction and recycling, increasing energy efficiency and the principles of a green economy. The importance of environmental culture and raising public awareness is also considered.